Arbitration Authority in Business Dispute Resolution in Indonesia - trinarti pasaribu; Habibi Natama Ritonga; Raja Brahma Sembiring; Nurhatifah Manurung; Ahmad Yani Anshori (ISNU Sumatera Utara, 2024)
Arbitration has become one of the important mechanisms in the resolution of business disputes in Indonesia, mainly due to its ability to provide a faster, more flexible, and confidential resolution compared to general courts. However, there are various legal issues related to the authority of arbitration, especially in terms of the implementation of the arbitration award and the involvement of the court in the execution process. This research aims to analyze the authority of arbitration in the resolution of business disputes in Indonesia, evaluate the effectiveness of the implementation of arbitration decisions, and discuss future developments in arbitration policies and regulations. This research uses a normative juridical method with a legislative approach, utilizing primary legal materials such as Law Number 30 of 1999 concerning Arbitration, as well as secondary legal materials in the form of journals, books, and scientific articles. The data analysis technique used is qualitative, which analyzes various legal rules and their implementation in arbitration practices in Indonesia. The results of the study show that the authority of arbitration in Indonesia has been regulated quite clearly through laws and regulations, although in practice there are obstacles in the execution of arbitral awards involving courts. In addition, the practice of arbitration in Indonesia continues to grow, but challenges remain related to competition with international arbitration bodies and the need for regulatory reform. The discussion of this research highlights the advantages and disadvantages of arbitration compared to the courts, the effectiveness of the implementation of arbitration decisions, and the direction of arbitration policies going forward, including the adoption of technology and harmonization with international standards. The conclusion of this study emphasizes that arbitration is an effective business dispute resolution mechanism, but it requires strengthening in the aspects of regulation and decision implementation. This research recommends policy reforms to strengthen arbitration mechanisms and encourage businesses to utilize arbitration as an efficient and effective solution.